Monitoring Postoperative Opioid Use Following Simple Arthroscopic Meniscectomy: A Performance-Improvement Strategy for Prescribing Recommendations and Community Safety. Issue 4 (18th December 2018) - Gardner, Vance; Gazzaniga, David; Shepard, Michael; Grumet, Robert; Rubin, Benjamin; Dempewolf, Michael; Bray, Camille; Prietto, Carlos
Abstract : Background: Orthopaedic surgeons are confronted with a difficult dilemma: managing acute pain postoperatively and balancing the risk of prescription opioid use. To our knowledge, a prospective performance-improvement project providing opioid-prescription recommendations based on the actual amounts of usual and customary medication consumed following simple knee meniscectomy has not been described. Methods: One hundred and two patients undergoing arthroscopic knee meniscectomy prospectively recorded postoperative pain medications in a pain journal. Arthroscopic procedures were performed at 2 centers by 9 fellowship-trained senior surgeons. Various usual and customary prescribing protocols were observed, and the amount of medication consumed was recorded. Prescription and over-the-counter pain medication, quantity, frequency, and visual analog scale (VAS) pain scores were collected. Results: One hundred and two patients filled a prescription opioid medication and were included in the study. A total of 3, 765 pills were prescribed, and a total of 573.5 were consumed. For the 102 patients who filled a prescription, the average time consuming opioid medication was 2 ± 2 days (range, 0 to 13 days) postoperatively. No cases of persistent use were recorded. Of the 102 patients who filled a prescription, 29.4% did not take any prescription opioids postoperatively. A total of 3, 191.5 pills (or 22, 183.75 morphine milligram equivalents [MME]) were unused and were potentially available to the community. Conclusions: Following simple knee arthroscopy, the amount of prescribed opioid medication exceeds the need for postoperative pain management. In general, 68% of patients require a maximum of 13 pills postoperatively for 6 days. Surgeons should adjust prescribing standards accordingly to limit the amount of prescription opioids available to the community. Furthermore, a comprehensive response to include increased patient screening and monitoring as well as opioid use and disposal education is recommended.